Border Performances: Politics, art and tourism where Norway meets Russia - Fors, Bjarge Schwenke (UiT Norges arktiske universitet, 2019)
This thesis deals with political, artistic and touristic performances on Norway’s border with Russia. Based on ethnographic research in and around the town of Kirkenes, the thesis demonstrates how the state border and the borderland are staged through these performances. On a more general level, it aims to identify, explore and increase our knowledge about the role of performances in the construction of state borders and borderlands. Adhering to Richard Schechner’s (2013) perspective on performances as being meaning-making practices, the border and the borderland are investigated as material phenomena as well as communicative social constructions. Similar to other border regions, the Norwegian-Russian borderland is marked by an intensive production of performances by local, national and international actors for local, national and international audiences. Throughout this thesis, these manifold border performances are analyzed within and across three fields: politics, art and tourism. It is argued that the border tends to be construed either as a bridge, marked by openness, connectedness, unity, and continuity, or as a barrier, marked by division, disunity, and discontinuity. Correspondingly, the borderland is also invested with meaning, morphed into a place of great significance – both as a unique transnational space, and as the dramatic interface between East and West.